A qualitative study to explore understanding and perception of sexual abuse among undergraduate students of different ethnicities - Jayapalan, Ashvini; Wong, Li Ping; Aghamohammadi, Nasrin (Elsevier, 2018)
Objective: To explore university students' understanding on sexual abuse and their perceptions on sexual abuse victims. Methods: A total of 14 focus group discussions were conducted and stratified into three different ethnic groups (Malay, Chinese and Indian). Participants were female undergraduate students (n = 75) from a public university in Kuala Lumpur, Malaysia. Results: Findings revealed ethnic variations in the understanding of sexual abuse. Although many considered sexual abuse to necessarily involve sexual intercourse, Chinese and Indians had a better understanding and were more broad minded towards what constituted sexual abuse. Malay participants were more conservative and emphasized on relifious ways to define sexual abuse. Majority of participants considered that females and children are more likely to be victim of sexual abuse. A person's improper dress code, being too attractive in appearance, mixing with the opposite sex, lack of awareness, disabilities, environmental and family factors predisposes a person to sexual abuse. Conclusion: There were ethnic disparities in understanding the meaning of sexual abuse and perception of sexual abuse victim. Malays held more conservative opinions compared to Chinese and Indians.